The Influence of Brand Trust on Brand Evangelism Through Brand Identification and Passion Among Apple Users - Aurelia, Azriil; Tajuddien, Rahadyan (Journal Economic Business Innovation, 2025)
Purpose: This research examines the relationship between brand trust and brand evangelism among Apple product users, with a focus on brand identification and brand passion as mediators.Method: The study used a quantitative research design by survey method. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to analyze the data and assess the interrelationships between variables.Findings: The results indicate that brand trust does not correlate directly with brand evangelism, but is a significant predictor of both brand identification and brand passion. Moreover, brand trust is related to brand evangelism through positive mediation of brand passion but not for mediation of brand identification. The research highlights the importance of emotional attachment to becoming a consumer advocate.Novelty: The current study sheds light on the subtle pathways across which brand trust reinforces brand evangelism, as well as elucidates a new perspective on the comparative mediating role of brand passion vs. brand identification.Implications: The theoretical implications indicate that in the context of strong perfect information asymmetric power dynamics, brands (i.e., Apple) can implement strategies to create emotional engagement with consumers. Most importantly, trusting initiatives that boost brand passion can drive loyalty and advocacy, providing your most powerful pipeline of brand evangelists